Prevalensi Antibodi IgM Anti-Salmonella pada Penderita Diduga Demam Tifoid di Rumah Sakit Puri Bunda, Denpasar Bulan April – Oktober 2014 - Binti Osman, Zulaikha; Mulyantari, Ni Kadek (E-Jurnal Medika Udayana; Vol 6 No 11 (2017): E-Jurnal Medika Udayana, 2017)
Typhoid fever is a systemic infection disease which is caused by Salmonella enteric serotype typhi, paratyphi A and paratyphi B. These two types of Salmonella can still be found widely in many developing countries especially those in tropical and subtropical region, which is now began developing around Bali, a well-known tourist-attraction place. Typhoid fever has become a public health concern because of its clinical presentations that can be misunderstood with other types of diseases or infections. Typhoid fever also can lead to numerous complications which make it a very serious condition that has become a global burden. The prevalency of S.typhi detected in febrile participants is highest in Indonesia. Research has been done using a cross-sectional plan, which uses a secondary data taken at the Clinical Pathology Laboratory at Puri Bunda Hospital. These are the laboratory results of the serological tests taken by the patients suspected with typhoid fever at Puri Bunda Hospital. The research was done for three months from August 2014 to October 2014, and the data were divided into age groups, sex and test scores. Among 116 samples collected, the highest number of patients belong to age group 2-20 years old, which is 82 samples. This age group also recorded the highest number of patients scoring a test score of ? 2, which shows a negative result, with 47 samples (63.5%). 23 samples are from the age group of 0-1-year-old (31.1%), 3 of them belong to 21-40 years old age group (4.1%) and 1.4% for age group >40 years old, detected with test score of ? 2. A borderline test result (score 3) shows the highest number of samples recorded are 11 (84.6%) which belongs to age group 2-20 years old. 15.4% of samples belong to age group 0-1-year-old and neither score 3 for age group 21-40 and >40 years old. Age group 2-20 years old recorded 23 samples (79.3%) for positive weak of typhoid fever (score 4), age group of 0-1-year-old with 6 samples (20.7%), 3 samples (2.6%) and 1 sample (0.9%) from the age groups of 21-40 years old and >40 years old respectively. For score ? 2, males have more numbers, 46 (55.4%) compared to females with 37 (44.6%). Male and female has the same percentage of samples collected with a test score 3 at borderline. For test score 4, a positive weak, there are 13 males (48.1%) and 14 females (51.9%) recorded. It is concluded that age group 2-20 years old have the highest prevalent of typhoid fever, meanwhile there is no significant different between males and females to have positive prevalency towards typhoid fever. There is a need for the research to be continued for a longer period of time to understand better on the dynamics and distribution data of typhoid fever in each month for a year. Keyword : Typhoid Fever, IgM, Salmonella typhi, Age, Gender, Test Score